How Can We Learn from Milieus? - Sabolius, Kristupas (Acta Paedagogica Vilnensia, 2025)
Environmental education requires a philosophical reevaluation. As evidence of this need, Humphreys and Blenkinsop (2017) note that educational theories remain fragmented due to the absence of strong philosophical foundations, while the educational discourse also lacks the coherence needed to transcend traditional disciplinary boundaries. Additionally, Sonu and Snaza (2016) argue that failing to question the assumptions underlying the concept of the human subject risks grounding the relationship between humans and the world in a ‘momentary ethic’, where partial knowledge is tied to accidental actions. In light of these critiques, it is clear that environmental education requires a philosophical reevaluation and rearticulation of issues such as entanglement to and with the individual. This paper argues that the abstract notion of ‘environment’, defined by its distinction from the individual, contrasts with the idea of ‘milieu’, which implies a connection to the individual, making the milieu a solid foundation for developing a philosophical theory of education. This argument is supported by bringing together theoretical and practical dimensions – namely, Gilbert Simondon’s theoretical concept of the ‘associated milieu’ and Phenomenon-Based Learning as a concrete educational practice. This approach not only identifies the individual as directly connected to the milieu but also demonstrates the potential to develop processes of connectedness to milieus as educational practices. In this respect, integrating philosophical insights with educational practices complements theories of environmental education, thereby creating an educational dimension which unites complex natural, cultural, and social phenomena.
Keywords: environmental education; environment; milieu; associated milieu; imagination; phenomenon-based teaching